Ethnicity, N. 5 : Ethnic Identities and Integration of the Society - (:unkn) unknown (Daugavpils Universitātes Sociālo pētījumu institūts, Latvijas Universitātes Filozofijas un socioloģijas institūts, 2011)
The articles published in this issue analyse the topic of ethnic identities and the integration of society.
Ethnicity – a peer-reviewed journal was established by the Institute of Social Investigations (Daugavpils University, Latvia) and the Institute of Philosophy and Sociology (University of Latvia). The journal publishes original works about ethnicity in different fields of knowledge – sociology, history, social linguistics, social psychology, law, political science.
Keywords: Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::Ethnology; ethno-linguistic groups; integration; ethnic identity; ethnicity; national alliance; minority groups; implementation of rights